2015
DOI: 10.1517/17460441.2015.1051963
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein-based drug discovery for treatment of atherosclerosis

Abstract: It is rational that the functionality of HDL is more important than the plasma HDL-C level in the evaluation of pharmacological treatment in atherosclerosis. HDL-based strategies designed to promote macrophage RCT are a major area of current drug discovery and development for atherosclerotic diseases. A better understanding of the functionality of HDL and its relationship with atherosclerosis will expand our knowledge of the role of HDL in lipid metabolism, holding promise for a future successful HDL-based the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…However, future studies that precisely assess the effect of other comorbidities and the effect of probable modifiers (e.g., gender) on this association are urgently needed. In addition, the impact of novel lipid‐lowering therapies on HDL composition and functionality, and the overall effect on cognitive function deserves scrutiny. Indeed, further investigations must determine whether HDL and related molecules play a causal role in the pathogenesis of neurodegenerative diseases or whether HDL represents an early‐stage biomarker of these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies that precisely assess the effect of other comorbidities and the effect of probable modifiers (e.g., gender) on this association are urgently needed. In addition, the impact of novel lipid‐lowering therapies on HDL composition and functionality, and the overall effect on cognitive function deserves scrutiny. Indeed, further investigations must determine whether HDL and related molecules play a causal role in the pathogenesis of neurodegenerative diseases or whether HDL represents an early‐stage biomarker of these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The potential anti-atherogenic effects of HDL have been linked to its main functional and structural protein, apolipoprotein A-I (ApoA-I) [ 4 ]. Amongst others, ApoA-I is the acceptor for ATP-binding cassette transporter (ABCA1)-mediated cholesterol efflux and as such, regulates cholesterol efflux capacity [ 5 ]. In addition, ApoA-I has many other functional and cardioprotective effects such as blunting inflammation [ 6 ] and lowering coagulant activity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent studies demonstrated that the level of circulating HDL-C alone represents an inadequate indicator of therapeutic efficacy ( 2 ). Instead, the functionality of HDL is more informative than circulating HDL-C levels in the evaluation of therapeutic approaches for atherosclerosis ( 3 ). HDL has multiple atheroprotective effects.…”
mentioning
confidence: 99%